White Blood Cell Count Mediates the Association Between Periodontal Inflammation and Cognitive Performance Measured by Digit Symbol Substitution Test Among Older U.S. Adults. (4th September 2020) - Li, An; Chen, Yuntao; van der Sluis, Luc W M; Schuller, Annemarie A; Tjakkes, Geerten-Has
Abstract: Background: Systemic effects of periodontal infection may increase the risk of central neuroinflammation, aggravating impaired cognition. This study aims to examine whether systemic inflammatory factors mediate the possible association between periodontal inflammation and cognitive function. Methods: We conducted a cross-sectional analysis of 766 participants aged ≥ 60 years and who had completed periodontal and cognitive examinations in the National Health and Nutrition Examination Survey (NHANES) 2001–2002. We used multivariable linear regression to investigate the overall association between periodontal health and cognitive function as measured by the digit symbol substitution test (DSST). Bleeding on probing (BOP) and periodontal inflamed surface area (PISA) were used to assess the periodontal inflammatory activity and burden, respectively. Mediation analyses were used to test the indirect effects of the BOP/PISA on DSST via C-reactive protein, white blood cell (WBC) count, and fibrinogen. Results: Participants with superior periodontal health obtained higher DSST scores than those with poorer periodontal health, adjusting for demographic factors and chronic conditions. Concerning the inflammatory activity, WBC count acted as a full mediator in the association between BOP and DSST (β = −0.091; 95% confidence interval [CI] = −0.174 to −0.008) and mediated 27.5% of the total association. Regarding the inflammatory burden, WBC count acted as a partial mediator in the association between PISA and DSST (β = −0.059; 95% CI = −0.087 to −0.031) and mediated 20.3% of the total association. Conclusion: Our study indicated the potential role of systemic inflammatory factors as a mediator of associations between periodontal inflammation and cognitive function in the U.S. geriatric population.